Hybrid load balancing approach for cloud environment. (2017) - Jain, Anurag; Kumar, Rajneesh
Cloud computing is the result of growth in networking and computer technologies in last few years. It focuses on providing scalable and reliable infrastructure for implementation of internet-based services. Its future depends on effective installation of infrastructure, efficient utilisation of resources and dynamic transformation of load. This will help in achieving better fault tolerance ratio and higher customer satisfaction. To distribute the workload dynamically across multiple nodes so that no server is either underutilised or overwhelmed, there is a need of efficient and effective load balancing strategy which should change itself dynamically according to environment and task. In this paper, authors have proposed a hybrid load balancing approach named JIMC by combining best features of some of the existing approaches. JIMC approach has been tested using cloud analyst simulator on various scenarios. It has been observed that JIMC approach is efficient in comparison to existing approaches and also prevent the system failure by giving warning of systems overloading in advance.